The Fallen Soldier as Fascist Exemplar: Military Cemeteries and Dead Heroes in Mussolini's Italy - Malone, Hannah (My University, 2022)
This article aims to dissect the nature of exemplarity in Italian Fascism. The social and political structures that emerged in Fascist Italy were highly reliant on a sense of morality, largely because of the degree of violence inherent in those structures. Under Fascism, morality was founded on concrete examples rather than on abstract principles. Exemplars were idealized sources of moral strength, and figures with the capacity to inspire or persuade. In particular, the fallen soldier and those who died for the nation constituted a major category of Fascist exemplars. Thus, soldiers who fell in the First World War were awarded exemplary status in order to encourage behaviors favorable to the regime. With the goal to demonstrate the importance awarded to exemplars, this paper focuses on a group of ossuaries, or bone depositaries, that were built under Mussolini’s dictatorship, and within which the regime reburied the remains of soldiers who fell in the First World War. The main purpose of the ossuaries was to present the dead as role models that might boost support for a program of nationalism, militarism, and imperialism. Thus, while their creation drew on factors such as Romantic literature and Italy’s religious and political traditions, the ossuaries represent an ideal case study of how Fascist morality was aided by and expressed through the use of exemplars.
PUBLISHED
Keywords: Fascist Italy; morality; death; cemeteries; exemplarity; Mussolini; Inclusive Society; European History; History of Architecture